Exploring the Role of Trust and User Experience on Users’ Continuance Intention in Digital Fund Transfers: A Mediated Model through User Satisfaction - Lastiati, Anies; Nurhipnudin, Iip (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid development of digital technology has transformed the way people conduct financial transactions, especially through mobile banking and e-wallet platforms such as DANA, OVO, GoPay, and FLIP. This study investigates the influence of trust and user experience on continuance use intention of digital fund transfer services, with user satisfaction serving as a mediating variable. A quantitative approach was employed, involving 100 respondents who actively use digital fund transfer services in the Jabodetabek area. Data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The findings reveal that both trust and user experience have significant direct effects on continuance use intention, and user satisfaction partially mediates these relationships. Trust was found to be the strongest predictor, highlighting the importance of perceived security, reliability, and integrity in sustaining usage. Positive user experience, including intuitive interfaces, responsive features, and efficient transaction processes, also significantly contributes to continued engagement. These results provide insights for digital financial service providers to enhance user satisfaction and loyalty by improving trust and user experience, thereby supporting sustainable adoption of digital fund transfer platforms.